Analysis and optimization of mono parabolic leaf spring material using ANSYS. (2020) - Kumar, Pradip; Matawale, Chhabi Ram
Abstract: This research paper describes the work carried out on a mono parabolic leaf spring of a mini loader truck (Tata Ace) with a GVW (gross vehicle weight) of 1550 kg. A leaf spring is simple form of spring, pervasively used for the suspension in automotives. In this paper analysis is done for leaf spring whose thickness varies from the centre to outer end in parabolic nature followed by mathematical equation of a parabola, hence it is named as parabolic leaf spring (PLS). The modeling and analysis of the leaf spring has done in CATIA V5 R20 and ANSYS 15. The finite element analysis of the leaf spring has been carried out by initially discretising the model and then applying the relevant boundary conditions under the static loading conditions. The results from FEA indicated that the red area close to shackle was undergoing maximum value of stress which may lead to failure of mono parabolic leaf spring. A comparison between the different materials of leaf spring has also been performed to study the influence of mechanical properties of different material of PLS, in order to find out the amount of maximum stress for different material. During the analysis of all the materials boundary condition and applied load are same.